How do we … integrate pathogen reduced platelets into our hospital blood bank inventory?. Issue 5 (18th March 2019) - Rutter, Sara; Snyder, Edward L.
Abstract : For more than 50 years there has been an ongoing effort to combat transfusion‐transmitted infections and provide patients with the safest possible blood. This initiative has driven much of the research within the transfusion community. Initial methods included screening donors for travel histories to banned areas and for high‐risk behaviors, but pathogen‐specific assays performed at the collection and manufacturing sites also have become key factors in assuring blood safety. Many of these have focused on donor and laboratory‐based screening for transfusion‐transmitted diseases, as evidenced by the hepatitis and human immunodeficiency virus screening in the 1970s, 1980s, and 1990s. More recently, this effort has expanded to develop donor screening assays to identify other blood‐borne pathogens, such as Zika and West Nile viruses and Babesia . Bacterial contamination of units of platelets (PLTs), however, remains a significant concern. In recent years, the Food and Drug Administration has approved rapid tests to identify bacterially contaminated PLT units in the blood bank before transfusion. Other supplemental methods have been developed, however, that aim to inactivate blood‐borne pathogen(s) present in the blood product, rather than to rely on our ability to identify and interdict contaminated and infected components. Pathogen reduction technology, as this is referred to, provides a proactive way to further reduce the risk posed by transfusion‐transmitted infections.